Effects of acupressure on progress of labor and cesarean section rate: randomized clinical trial - Mafetoni, Reginaldo Roque (Rev Saude Publica, 2015)
OBJECTIVE: To analyze the effects of acupressure at the SP6 point on labor duration and cesarean section rates in parturients served in a public maternity hospital. METHODS: This controlled, randomized, double-blind, pragmatic clinical trial involved 156 participants with gestational age ≥ 37 weeks, cervical dilation ≥ 4 cm, and ≥ 2 contractions in 10 min. The women were randomly divided into an acupressure, placebo, or control group at a university hospital in an inland city in the state of Sao Paulo, Brazil, in 2013. Acupressure was applied to the SP6 point during contractions for 20 min. RESULTS: The average labor duration was significantly different between the SP6 acupressure group [221.5 min (SD = 162.4)] versus placebo [397.9 min (SD = 265.6)] and versus control [381.9 min (SD = 358.3)] (p = 0.0047); however, the groups were similar regarding the cesarean section rates (p = 0.2526) and Apgar scores in the first minute (p = 0.9542) and the fifth minute (p = 0.7218) of life of the neonate. CONCLUSIONS: The SP6 acupressure point proved to be a complementary measure to induce labor and may shorten the labor duration without causing adverse effects to the mother or the newborn. However, it did not affect the cesarean section rate.